Influence of Conventional and Ultrasonic-Assisted Extraction on Phenolic Contents, Betacyanin Contents, and Antioxidant Capacity of Red Dragon Fruit (Hylocereus polyrhizus) - Nurul Shazini Ramli; Patimah Ismail; Asmah Rahmat (The Scientific World Journal)
The aim of this study was to examine the effects of extraction methods on antioxidant capacities of red dragon fruit peel and flesh. Antioxidant capacities were measured using ethylenebenzothiozoline-6-sulfonic acid (ABTS) radical cation assay and ferric reducing antioxidant power assay (FRAP). Total phenolic content (TPC) was determined using Folin-Ciocalteu reagent while quantitative determination of total flavonoid content (TFC) was conducted using aluminium trichloride colorimetric method. Betacyanin content (BC) was measured by spectrophotometer. Red dragon fruit was extracted using conventional (CV) and ultrasonic-assisted extraction (UE) technique to determine the most efficient way of extracting its antioxidant components. Results indicated that UE increased TFC, reduced the extraction yield, BC, and TPC, but exhibited the strongest scavenging activity for the peel of red dragon fruit. In contrast, UE reduced BC, TFC, and scavenging activity but increased the yield for the flesh. Nonetheless, UE slightly increases TPC in flesh. Scavenging activity and reducing power were highly correlated with phenolic and flavonoid compounds. Conversely, the scavenging activity and reducing power were weakly correlated with betacyanin content. This work gives scientific evidences for the consideration of the type of extraction techniques for the peel and flesh of red dragon fruit in applied research and food industry.